SOSIALISASI HASIL PERENCANAAN TEKNIS JARINGAN DISTRIBUSI AIR BERSIH DESA CIPAGERAN, KOTA CIMAHI, JAWA BARAT - .Cahyana, Gede. H; Muchamad, Arief Nur; Novia, Fanny; Prajati, Gita; Mulyani, Tri; Febrion, Churchil; Susanto, Arif; Herliana, Erika (LPPM UKRI, 2025)
The availability of clean water is a crucial aspect of water security efforts to achieve national resilience. However, several regions in Indonesia still experience limited clean water supply in terms of quantity. Cipageran Village is one of the area that experienced limited clean water supply. Clean water distribution in the area is still inadequate. Therefore, residents of Cipageran Village drill wells to obtain clean water. Clean water sourced from these wells requires planning for distribution to residents' homes. Therefore, a technical plan for the clean water distribution network from the drilled wells to residents' homes is needed. The results of the technical planning for the clean water distribution network using the Epanet 2.2 software were then socialized to residents. In addition, the budget plan required to build the clean water distribution network was also delivered to residents. This socialization was expected to provide residents with the information needed to build a clean water distribution network from the drilled wells to residents' homes.